Konsep Dasar Manajemen Sumber Daya Manusia - Ikram Barman Maulana Sya'ban; Desi Dahliani; Muhammad Rezky; Machdum Bachtiar (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Human Resource Management (HRM) is a key strategic element in modern organizations, functioning as a primary system for managing human capital to achieve goals effectively and efficiently. In today’s era of rapid technological change, global competition, and shifting workforce dynamics, HRM is no longer viewed as a purely administrative function. Instead, it has evolved into a proactive and strategic partner that contributes directly to organizational success. This study examines core HRM concepts, including human resource planning, recruitment, employee development, performance evaluation, compensation management, and industrial relations. Using a qualitative approach through library research, this paper draws on various academic sources, books, and journals to understand effective HRM practices. The findings show that when these HRM processes are implemented in an integrated and systematic way, they help create a workforce that is skilled, adaptable, and competitive. In addition, organizations that apply strategic HRM approaches tend to experience better productivity, stronger employee engagement, higher retention rates, and improved long-term performance. Overall, this study highlights that understanding and applying HRM principles is essential for building a positive work environment. Aligning HR strategies with organizational goals enables companies to achieve sustainable growth and remain resilient in a dynamic business environment..